Research on irregular plane mid story isolation structures in castor earthquake prone areas considering SSI effect - Xiao, Shuai; Li, Cheng; Liu, Dewen; Sun, Weiwei; Lei, Min (Frontiers in Earth Science, 2023)
The rock composition of karst area is mainly limestone, which is easy to be eroded and dissolved by water, forming a complex and fragile tectonics. Under the action of earthquake, the instability of stratum is aggravated. The mid story isolation structure is a new type of isolation structure developed from the basic isolation structure, and irregular mid story isolation buildings are highly susceptible to adverse seismic conditions. Previous studies have mostly adopted the assumption of rigid foundations, neglecting the influence of soil on irregular structures. In order to study the seismic response of isolated structures in irregular planes in karst earthquake prone areas considering soil structure interaction, a finite element model of isolated structures in irregular planes considering soil component interaction was established, and the seismic response of the structure under rigid foundation was calculated. Soft and hard soil foundations were studied, and compared with structures without considering SSI effect. Research shows that when considering the SSI effect, the seismic response of the structure increases and the damage to the structure intensifies; When considering SSI, the seismic response of soft soil is greater than that of hard soil, and the softer the soil, the more obvious it becomes; After considering the SSI effect, the torsional effect caused by the irregularity of the plane increases; The design of building structures should fully consider the adverse effects of soil layers on the seismic response of structures under plane interlayer seismic irregularities. In the design of building structures, it is necessary to fully consider the adverse effects of irregular planes on the seismic response of the structure. This consideration is particularly important in the design of soft soil high-rise buildings in karst earthquake areas to prevent unsafe designs and consider the SSI effect in actual seismic resistance.